The association between use of social media and the development of body dysmorphic disorder and attitudes toward cosmetic surgeries: a national survey - Khadijah Ateq; Khadijah Ateq; Mohammed Alhajji; Mohammed Alhajji; Noara Alhusseini (Frontiers Media S.A., 2024)
IntroductionBody dysmorphic disorder (BDD) causes distress due to one's negative appraisal of their body image. The development of BDD has been linked to the passive use of social media and photo-editing apps. People with BDD typically pursue cosmetic surgeries to remedy their perceived flaws. The dramatic increase in the use of photo-editing apps and their well-established effects on mental health is a public health concern.PurposeTo study the association between use of social media and the development of BDD and acceptance toward cosmetic surgeries (ACSS) among Saudis.MethodsAn online, cross-sectional, validated survey conducted among Saudis 18 and older. Descriptive analyses were utilized for demographics and prevalence rates of main study variables. ANOVA was used to compare mean scores in BDD and ACSS among different demographic groups. Tukeys post-hoc test was done to identify the categories that were different when the ANOVA test showed a statistically significance. A p-value of <0.05 was considered statistically significant.ResultsA total of 1,483 Saudi adults completed the questionnaire. Key results showed that BDD was found in 24.4 % of the sample. The percentage of participants with BDD who spent 4-7 h per day on Instagram and Snapchat (29%) was significantly higher than those who spent only less than an hour per day on these platforms (19%) (p < 0.001). Individuals with BDD had a significantly higher risk of accepting cosmetic surgery compared to those without BDD (p < 0.001).ConclusionA growing body of evidence suggests that social media may impact mental health in different ways. This study reveals that heavy use of these platforms is associated with negative appraisals about one's physical appearance, and it fosters one's tendency toward cosmetic surgery, especially among females.